Response, Irradiated. Issue 1 (April 2021) - Cassels, Imogen
Abstract : Responding to Clive Scott's 'Vocativity and Dialogue in the Process of Reading for Translation', this essay centres on Scott's expansive definitions for prosody as both condition and direction for a translator's progress. Taking what Scott terms an 'irradiation of the spirit' as a key facilitates both an understanding of a text's projected half-lives through time, and potential for radical semantic decay, but also the expression of translation as an act of or with faith, an intimate and involved solidarity with the lived experience of reading and of being read.